Characterization of a monoclonal antibody against surface coat of infective larvae of Brugia malayi. - Soeyoko, Soeyoko (Universitas Gadjah Mada, 1995)
Malayan filariasis is an important public health problem in Indonesia. A diagnosis of filariasis is normally based on clinical, parasitological and immunological examinations but the methods have limitations. There is an urgent need to improve immunodiagnostic techniques for malayan filariasis using monoclonal antibodies to detect circulating antigen. Recently, many types of monoclonal antibodies have been produced following immunization of mice with various stages of filarial antigens. Those monoclonal antibodies have different characteristics.The objective of this study was to explore the characteristic of specific monoclonal antibodies against the surface coat of infective stages of Brugia malayi larvae.This monoclonal antibody recognized antigen of 40.000 MW protein which is present among the antigens of surface coat of Brugia malayi larvae, as detected by an immunoblotting technique. Classification using EUSA techniques indicates that those antibodies are IgGi, IgG2b and IgG3 subclasses. In addition, these antibodies also demonstrate a low level reactivity with surface antigen of Brugia pahangi, Ascaris lumbricoides and hookwormKey words : surface coat - infective larvae - monoclonal antibody - circulating antigen - Brugia malayi